Development of a Magnetization Device to Magnetize Cutting Fluids in the Flowing State During the Metal Cutting Process (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In this paper, special magnetic treatment device to magnetize flowing lubricating cooling fluids during the metal cutting process is developed. Analysing results show that it is possible to create a special lubricating-cooling technological environment by magnetizing cutting fluids with a high magnetic field in their flowing state in machining. Developed device has an important impact on metal cutting process performances.